Sustainable Development of Sea-Corridors and Coastal Waters : The TEN ECOPORT project in South East Europe - Stylios, Chrysostomos; Floqi, Tania; Marinski, Jordan; Damiani, Leonardo (Springer International Publishing : Imprint: Springer, 2015)
Edited in collaboration with TEN ECOPORT project, this volume contains the proceedings of the 1st International Conference on 'Sustainable Development of the Sea-corridors and Coastal Waters'. The book highlights the advances of environmental pollution management on ports and coastal zones. Particular attention is given to water quality, issues that concern the marine environment of sea corridors and coastal waters, especially in regions surrounding ports. In addition to these topics the chapters explore novel methodologies and technologies, IT solutions, data and instrumentation of monitoring water quality. The book is organized into five parts: assessment, monitoring, sustainable management system, port processes and historical ports.   TEN ECOPORT (Transnational ENhancement of ECOPORT8 network) is a project co-financed by the South East Europe Transnational Cooperation Programme. For more information please see http://www.tenecoport.eu/).